Effect of blood transfusion in combination with plasmex-D-40 and hypertonic saline on biochemical profiles of endotoxaemic buffalo calves - Singh, D Y; Singh, R Y; Sodhi, S P S (The Indian Journal of Animal Sciences, 2011)
Buffalo calves (10) divided into 2 groups of 5 animals each were subjected to the i/v infusion of EschericlJia coli endotoxin @ 511g/kg BW for 3 h. Group 1 was kept untreated and observed for 4 h subsequent to endotoxin infusion. This group showed a significant hypoproteinemia, hypoalbuminemia along with a very prominent hypoglycaemia, hypochloraemia and decrease in plasma creatinine while the plasma globulin and other proteins. Sodium and potassium concentrations altered nonsignificantly. The group 2 animals had the same protocol till 3 h but at the end of endotoxin infusion, these animals were treated with i1v infusion of 7.2% hypertonic saline solution @ 4ml/kg BW followed by plasmex-D~40 @ 10ml/kg BW and whole blood @ 20mllkg BW as one time infusion. These animals showed no transfusion reaction after treatment and lay quiet with eyes open. The plasma total proteins, globulins and other proteins, chloride, sodium and potassium varied nonsignificantly but a significant hypoalbuminemia, hypoglycemia and fall in creatinine was observed.The results indicated that the blood transfusion although is beneficial for total protein, chloride and haemodynamic parameters yet it does not significantly compensate the albumin, glucose and creatinine. The lower circulating levels of all these may be due to haemodilution caused by infusion of hypertonic saline and dextran-40 as these cause shift of extra-cellular fluids into the circulation.